Secondary Metabolite Profiling of Species of the Genus Usnea by UHPLC-ESI-OT-MS-MS - Francisco Salgado; Laura Albornoz; Carmen Cortéz; Elena Stashenko; Kelly Urrea-Vallejo; Edgar Nagles; Cesar Galicia-Virviescas; Alberto Cornejo; Alejandro Ardiles; Mario Simirgiotis; Olimpo García-Beltrán; Carlos Areche (Molecules, 2017)
Lichens are symbiotic associations of fungi with microalgae and/or cyanobacteria, which are considered among the slowest growing organisms, with strong tolerance to adverse environmental conditions. There are about 400 genera and 1600 species of lichens and those belonging to the Usnea genus comprise about 360 of these species. Usnea lichens have been used since ancient times as dyes, cosmetics, preservatives, deodorants and folk medicines. The phytochemistry of the Usnea genus includes more than 60 compounds which belong to the following classes: depsides, depsidones, depsones, lactones, quinones, phenolics, polysaccharides, fatty acids and dibenzofurans. Due to scarce knowledge of metabolomic profiles of Usnea species (U. barbata, U. antarctica, U. rubicunda and U. subfloridana), a study based on UHPLC-ESI-OT-MS-MS was performed for a comprehensive characterization of their secondary metabolites. From the methanolic extracts of these species a total of 73 metabolites were identified for the first time using this hyphenated technique, including 34 compounds in U. barbata, 21 in U. antarctica, 38 in U. rubicunda and 37 in U. subfloridana. Besides, a total of 13 metabolites were not identified and reported so far, and could be new according to our data analysis. This study showed that this hyphenated technique is rapid, effective and accurate for phytochemical identification of lichen metabolites and the data collected could be useful for chemotaxonomic studies.